Extent of Trial of Improved Designs of Lobster Traps - KAUL, P. N.; KANDORAN, M. K. (Fishery Technology, 2017)
The mean extent of trial of an improved design of lobster trap by 45 fishermen was26.46. The cost oflocal traps and number of seasons used were both significantly negatively associated with the extent of trials; its relationship with the annual catch by indigenous trap approached significance. These three variables accounted for 59 % of the variance in the extent of trial.